2021
DOI: 10.1111/jmwh.13203
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and Influenza Vaccine: A Review

Abstract: Influenza is a highly contagious, deadly virus, killing nearly half a million people yearly worldwide. The classic symptoms of influenza are fever, fatigue, cough, and body aches. In the outpatient setting, diagnosis can be made by clinical presentation with optional confirmatory diagnostic testing. Antiviral medications should be initiated as soon as possible, preferably within 24 hours of initiation of symptoms. The primary preventive measure against influenza is vaccination, which is recommended for all peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 39 publications
1
79
0
3
Order By: Relevance
“…This has been reported for other viruses such as influenza, since seasonally, one of the hemispheres develops a variant, and later, it is transmitted to the other hemisphere [97,98]. This is also due to the RNA structure of the influenza virus, with a high mutation capacity, which is why vaccination campaigns with vaccines including new influenza variants are performed every year [99]. This has already been observed in some studies that showed these differences between the different continents.…”
Section: Predisposing Geographical Environmental and Genetic Conditions For The Development Of Sars-cov-2 Variantsmentioning
confidence: 64%
“…This has been reported for other viruses such as influenza, since seasonally, one of the hemispheres develops a variant, and later, it is transmitted to the other hemisphere [97,98]. This is also due to the RNA structure of the influenza virus, with a high mutation capacity, which is why vaccination campaigns with vaccines including new influenza variants are performed every year [99]. This has already been observed in some studies that showed these differences between the different continents.…”
Section: Predisposing Geographical Environmental and Genetic Conditions For The Development Of Sars-cov-2 Variantsmentioning
confidence: 64%
“…[5,6] Influenza viruses are also known to cause infectious respiratory diseases in humans and these can be mistaken for COVID-19 owing to the similarity in symptoms: cough, fever, fatigue and muscle pain. [7,8] However, unlike COVID-19, the symptoms of influenza usually arise within 1-4 days following an infection. [9] While influenza is considered to be less threatening to the public than COVID-19, with 0.29-0.65 million annual deaths globally according to the WHO, [10] it can be severe and life-threatening in children, the elderly and people suffering with other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although influenza B is less infectious, its severity and mortality rate are comparable to those of type A. [12] As the symptoms of COVID-19 and influenza are similar, [7] there is a need for a single-swab SARS-CoV-2 and influenza A/B combination test that can distinguish between these infections. This could facilitate appropriate clinical responses from healthcare professionals to target treatment and containment effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza vaccination is the preferred and most cost-effective intervention tool currently available to prevent influenza virus infection and disease. Licensed influenza vaccines include inactivated whole or split viruses, (recombinant) viral subunit, and live attenuated vaccines [ 5 ]. Seasonal influenza vaccines contain viral strains or hemagglutinins (HAs) closely related to the putative upcoming seasonal strains of influenza A viruses and influenza B viruses.…”
Section: Introductionmentioning
confidence: 99%